Foundation Funding of the Environmental Movement. (November 2017) - Jenkins, J. Craig; Carmichael, Jason T.; Brulle, Robert J.; Boughton, Heather
We address the long-standing debate between elite theorists and pluralists about the priorities and scale of foundation funding for social movements by examining systematic data on foundation grants to environmental movement organizations (EMOs) between 1961 and 2000. By combining these data with a comprehensive inventory of EMOs that operated in this period, we show that foundation giving favored conservative mainstream environmental discourses, EMOs that avoided protest, older EMOs, and those located in the northeastern seaboard. Despite major growth in the constant dollar value of foundation giving to EMOs, this remains a highly concentrated system of philanthropy with over half of all foundation grants going to the top 20 grant recipients, a third of which have been leading recipients for over five decades. Nonetheless, there is evidence of change in that alternative discourses, especially environmental justice, received over 5% of these grants in 2000.